A Multilateral Model of Trade-Balancing Tariff Concessions - Baldwin, Robert E.; Lage, Gerald M. (The Review of Economics and Statistics, 1971)
A UNIQUE feature of the Kennedy Round of the General Agreement on Tariffs and Trade (GATT) Negotiations (1964-1967) was the use of the technique of reducing tariffs. Under a linear approach each participant agrees to make a uniform across-theboard percentage cut in import duties, subject only to a bare minimum of exceptions and to the condition that the country achieves overall reciprocity. This approach was adopted in an effort both to reduce the time and effort involved in traditional item-by-item negotiations and to achieve a deeper average duty-cut for all participants. In prior negotiations under the GATT, the bargaining technique was essentially bilateral. Request and offer lists were exchanged between all pairs of countries and bargaining then proceeded on a two-by-two basis. In order to make this type of negotiation feasible, the so-called principal supplier rule was followed. A country's offer list to another country covered only those items for which the other country was the principal or at least, a very important import supplier.1 This procedure minimized the problem of conducting simultaneous negotiations on the same item by different country teams. At times during the negotiations, however, information concerning concessions tentatively agreed upon in the independent bilateral negotiations was made available to all pair-wise teams so that each might evaluate the indirect effects of the other negotiations on its bilateral balance of concessions. Finally, when each pair of countries had reached a mutually satisfactory balance of concessions, the list of offers by a country to each other country was combined into a single tariff reduction list that applied to all countries. Just what constituted a satisfactory balance of concessions or reciprocity was never openly defined, but it came to mean that a country would achieve an approximately equal increase in exports from the concessions it obtained as the increase in imports from the concessions it granted.2 The main concern of negotiators was to achieve this reciprocity on the total trade of their country with the rest of the world. However, since the negotiations were conducted mainly on a bilateral basis, the notion of reciprocity also tended to dominate the pair-wise negotiations between countries. As became increasingly apparent through successive GATT negotiating rounds, following the principal supplier rule and imposing a condition of approximate bilateral balance for changes in the volume of trade considerably limited the set of feasible total increases in exports and imports. The early hopes of many Kennedy Round negotiators that most of the difficulties connected with the item-by-item, bilateral negotiating technique would be eliminated by following a linear-cut rule proved to be much too optimistic. Some industrial countries, namely Canada and Australia, as well as all the less developed countries did not accept the linear rule. More disappointing, however, was the reluctance of most major countries to cut agricultural duties on a linear basis and the insistence of the European Economic Community (EEC) on a special rule to handle significant disparities in tariff rates of various countries on the same item.3 Lists of exceptions for certain countries also proved to be larger than was hoped for initially. Once it became apparent that reciprocity could not be achieved by bargaining on a